TOURISM INTEGRATION AMONG CENTRAL ASIAN COUNTRIES: OPPORTUNITIES AND CHALLENGES (Journal of Multidisciplinary Sciences and Innovations, 2025)
Tourism integration among Central Asian countries holds great potential for enhancing regional cooperation, economic development, and global competitiveness. The rich cultural heritage, historical ties, and geographical proximity of Kazakhstan, Uzbekistan, Kyrgyzstan, Turkmenistan, and Tajikistan create favorable conditions for cross-border tourism development. However, this process faces several challenges, including visa restrictions, limited infrastructure, lack of unified marketing strategies, and political coordination issues. This article explores the opportunities for tourism integration in the region, identifies key obstacles, and proposes recommendations to strengthen collaboration. Emphasis is placed on the role of joint initiatives, digital solutions, and institutional frameworks to enhance sustainable and competitive tourism growth in Central Asia.